The Effect Of Debt To Equity Ratio, Current Ratio, And Firm Size On Price To Book Value - Pratama, Dicky Leumardi; Saefudin, Ayi Achmad; Agung Yulianto (Cita konsultindo, 2025)
The price-to-book ratio is a metric utilized to assess if a stock is overvalued or undervalued in comparison to other equities. This study aims to determine how the influence of Debt to Equity Ratio, Current Ratio, and Firm Size on Price to Book Value. This study uses secondary data obtained from the company's annual report accessed through www.idx.co.id and the company's official website. This study examined 13 automotive sub-sector companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2023. The sample selection method in this study was purposive sampling, namely the samples used in this study had to meet the sample criteria and obtained 6 companies that were sampled with an observation period of 6 (six) years so that 36 samples were obtained in this study. The data analysis methods used in this study are descriptive statistics, classical assumption tests, multiple regression analysis, hypothesis testing, and the coefficient of determination. The findings of this study demonstrate that the Debt to Equity Ratio and Current Ratio do not influence Price to Book Value, however Firm Size does impact Price to Book Value.